Additive manufacturing of zirconia parts with organic sacrificial supports. Issue 4 (5th May 2020) - Li, Wenbin; Armani, Amir; McMillen, Devin; Leu, Ming; Hilmas, Gregory; Watts, Jeremy
Abstract: Ceramic On‐Demand Extrusion (CODE) process has been recently proposed for additive manufacturing of strong ceramic components via extrusion. This paper focuses on fabricating 3 mol% yttria‐stabilized zirconia (3YSZ) components using CODE process, and enabling CODE to produce parts with support structures. A colloidal suspension of 3YSZ was developed and deposited through the main nozzle, and an organic feedstock was developed and deposited by means of another nozzle to fabricate supports. After printing and drying of raw parts, supports were removed by increasing the temperature and parts were then sintered to near theoretical (~99%) density. The maximum overhang angle that could be built with no support was also found out to be approximately 60 degrees. Three organic support materials, that is, polycaprolactone (PCL), silicone, and petrolatum were prepared and tested. PCL and petrolatum were identified as feasible support materials. Specimens were fabricated to validate the efficiency of the support materials and to evaluate CODE's capability for building parts with complex geometry. The microstructures of these parts were also analyzed via scanning electron microscopy.